2010
DOI: 10.1007/s10597-010-9362-9
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice System Involvement Among People with Schizophrenia

Abstract: There is growing concern that people with schizophrenia and other severe mental illnesses are increasingly at risk for unnecessary criminal justice system (CJS) involvement. There has been limited examination, however, of which individual characteristics predict future CJS involvement. This study uses data from the Clinical Antipsychotic Trials of Intervention Effectiveness on sociodemograhic characteristics, baseline clinical status, and service use among patients diagnosed with schizophrenia to prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 84 publications
0
14
0
2
Order By: Relevance
“…An Australian study found that only those people with a mental illness and a co-occurring substance use, and those people with substance use problems alone had significantly higher offending and incarceration rates compared to people with a mental health impairment who did not use substances (NSW Bureau of Crime Statistics and Research, 2010). The relationship between substance use, offending and schizophrenia has also been demonstrated in several studies, including studies where drug and/or alcohol use was identified as the most significant variable in relation to offending (Fazel & Yu, 2011;Greenberg et al, 2011;Mullen, Burgess et al, 2000). Recent work found there is a primary link between schizophrenia, substance use and offending, and also proposes some tentative suggestions about links between substance use, paranoid symptoms, command hallucinations and offending (Heinrichs & Sam, 2012).…”
Section: Criminal Justice Involvement Of People With Mental Illnessmentioning
confidence: 82%
See 4 more Smart Citations
“…An Australian study found that only those people with a mental illness and a co-occurring substance use, and those people with substance use problems alone had significantly higher offending and incarceration rates compared to people with a mental health impairment who did not use substances (NSW Bureau of Crime Statistics and Research, 2010). The relationship between substance use, offending and schizophrenia has also been demonstrated in several studies, including studies where drug and/or alcohol use was identified as the most significant variable in relation to offending (Fazel & Yu, 2011;Greenberg et al, 2011;Mullen, Burgess et al, 2000). Recent work found there is a primary link between schizophrenia, substance use and offending, and also proposes some tentative suggestions about links between substance use, paranoid symptoms, command hallucinations and offending (Heinrichs & Sam, 2012).…”
Section: Criminal Justice Involvement Of People With Mental Illnessmentioning
confidence: 82%
“…While there is ongoing unresolved debate in the literature as to the relationship between untreated mental illness and criminal justice involvement (Greenberg et al, 2011), there is a high level of consensus that cooccurring mental health and substance use disorders place individuals at high risk of reoffending and reincarceration Messina et al, 2004;Proctor & Hoffmann, 2012;Swartz & Lurigio, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations